REORIENTASI MANAJEMEN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DAN DERADIKALISASI AGAMA - Syukur, Fatah (WALISONGO, 2015)
Islamic religious education in schools substantively had a very important role. Inaccordance with the mandate of the Law on National Education System, religiouseducation should be provided to learners at all levels of education. Religiouseducation was expected not only to provide knowledge of religion, but also buildthe personality character of the students using religious values taught. Throughquantitative research, this study examined the implementation of Islamic religiouseducation in schools with the research problems: is there any correlation withreligious observance, and any other factors that affect the behavior of religion?How does the orientation of Islamic religious educationin schools? The resultsshowed that Islamic education is not positively correlated to the level of religiousobservance. Similarly, differences in men and women are not correlated to thelevel of religious observance. Therefore, there will be necessary reorientation ofreligious education in schools.***Pendidikan agama Islam di sekolah secara substantif memiliki peran yang sangatpenting. Sesuai dengan amanat Undang-undang Sistem Pendidikan Nasional,bahwa Pendidikan Agama harus diberikan kepada peserta didik di semua jenjangpendidikan. Diharapkan Pendidikan Agama bukan hanya memberikan pengetahuanagama saja, akan tetapi juga membentuk karakter kepribadian anak didikdengan nilai-nilai yang diajarkan oleh agama. Melalui penelitian kuantitatif, tulisanini mengkaji pelaksanaan Pendidikan Agama Islam di sekolah, apakah adakorelasinya dengan ketaatan beragama, adakah faktor-faktor lain yang berpengaruhterhadap perilaku beragama? Serta Bagaimana orientasi PendidikanAgama Islam di sekolah?. Hasil penelitian ini menunjukkan bahwa PendidikanAgama Islam tidak berkorelasi positif terhadap tingkat ketaatan beragama.Demikian pula perbedaan laki-laki dan perempuan tidak berkorelasi terhadaptingkat ketaatan beragama. Oleh karena itu, maka perlu ada reorientasi Pendidikan Agama di sekolah.